Dilemma Regarding the Scope of Projects in The Development of Key Educational Competences of Pre- school children - Kravarušić, Vesna B. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2023)
Conscious education, as a deliberate, planned and organized pedagogical process ensures the acquisition of knowledge, skills and habits in the function of developing learning, expanding and enriching human cognition. At the preschool age, education, through the development of general and special preparations, enables the child to perform life’s functions, humanize his nature and adopt and cultivate the foundations of the culture of civilization. The base for the transfer of material and spiritual values of the community is made up of sociocultural systems: symbolization and communication, systems of knowledge from science, technique, technology, work and production, artistic forms of expression, value and ethical attitudes. Through models of daily living, forms of play and learning, the child masters the program of preschool upbringing and education, which should eventually develop their competencies (through learning to learn - for the mother language and another language, mathematical, scientific, technological, digital, social knowledge, cultural awareness and initiative). Research with the aim of improving the projects was carried out using a descriptive method, analyzing the content of ten published projects, which identified their characteristics: educational content, types and combinations of implemented activities, used educational methods and specific educational competencies that were supported. The results speak of the use of limited educational contents of only one educational area, weak integration of contents, no changes in the application of the methodical repertoire (compared to the period until 2018) and favoring the development of children’s scientific competences.